A rolling horizon planning approach for short-term demand supply matching - Raphael Herding; Lars Mönch (Central European Journal of Operations Research, 2023)
Demand fulfillment and order management are important functions in semiconductor supply chains to interact with customers. In this paper, an iterative short-term demand supply matching (STDSM) algorithm based on mixed-integer linear programming (MILP) is proposed. This approach repromises orders taking into account the finite capacity of the shop floor. Decomposition is used to obtain computationally tractable subproblems. The STDSM approach is applied together with master planning and allocation planning in a rolling horizon setting. A simulation model of a simplified semiconductor supply chain is used for the rolling horizon experiments. The experiments demonstrate that the proposed STDSM scheme outperforms conventional business rule-based heuristics with respect to several delivery performance-related measures and with respect to stability.
Keywords: 650; Demand fulfillment; Short-term demand supply matching; Rolling horizon; Semiconductor supply chains; Discrete-event simulation